An evaluation of classical morphologic and morphometric parameters reported to distinguish wolves and dogs. (February 2019) - Janssens, Luc; Perri, Angela; Crombé, Philippe; Van Dongen, Stefan; Lawler, Dennis
Abstract: Morphological and morphometric bone variation between archaeological wolves and the oldest domestic dogs commonly are used to define species differences. However, reference data often have been based on small numbers, without robust statistical support. We consulted the literature on these matters in all possible languages and tested many of the proposed species differences by examining wolf and dog skeletons from several collections, accompanied by an extensive synthesis of existing literature. We thus created large reference groups, assessing data distributions and variability. We examined mandible height, width, length, and convexity; contact points of the skull on a horizontal plane; caudal shifting of the border of the hard palate; skull size; carnassials tooth size reduction; micro-anatomical differences in teeth, snout, and skull height; and snout length and width. Our results show that skull length and related size; skull height; snout width; orbital angle; P4 and M1 mesio-distal diameter can help (albeit to a limited extent) to distinguish the oldest archaeological dogs from wolves. Based on our observations, we re-evaluated recent large Pleistocene canids reported as Paleolithic dogs and concluded instead that they fit well within the morphomentric distributions seen with Pleistocene wolves. The research presented here reflects the recent trend to critically re-evaluate axiomatic assumptions about wolf-dog differences, and to rephrase the morphological and morphometric definition of an early archaeological dog in a more suitable manner. These results are important to the international archaeological community because they place historical reports in a newer context, and create a robust (although narrow) framework for further evaluation of archaeological dogs and wolves. Highlights: We tested classical morphometric criteria, generally accepted to discern archaeological dogs and wolves. Most criteria were proved to be non-diagnostic. P4 mesio-distal diameter and skull length are diagnostic, four other criteria are helpful but only in extreme values or means. Upper-Paleolithic proto-dogs are not different from contemporary wolves.